Fenologia, produccion y contenido de almidon en arboles de mango en Guanacaste, Costa Rica - Gamboa Porras, J.M.=700 1 Marin Mendez, W.
(Es, En)
Ilus., 37 ref.
Keywords: MANGIFERA INDICA; FENOLOGIA; PRODUCCION; CRECIMIENTO; PERIODO VEGETATIVO; FLORACION; VARIEDADES; COSTA RICA; MANGO; VARIEDAD TOMMY ATKINS